A descriptive study on the beliefs regarding oral health care of adolescents of Manila Science High School - Cruz, Elmarie Q.; Suarez, Jonna Monina G.; Yumul, Giselle S. (Adviser).
Researchers have supported the fact that health beliefs play an important role in the determination of a person's health-related behavior. A set of favorable oral health care beliefs has been found to influence an individual's oral health for the better, which consequently helps in the attainment of an optimum quality of life. Through a questionnaire adapted from the study of Borkowska et al in 1998, which asks subjects to state whether they agree or disagree with statements about oral health, this study aims to describe the set of prevailing beliefs on oral health care that the adolescents of today presently possess and to determine the adequacy of such beliefs. The statements were divided into two groups: the positive statements and the negative statements. The results of the study show that there are 47.05% respondents who strongly agree, 46.78% agree, 5.67% disagree, and 0.49% strongly disagree to the positive group of statements. To the negative group of statements, 4.90% strongly agree, 17.75% agree, 54.91% disagree, and 22.44% strongly disagree. This findings present a trend towards favorable responses to the beliefs, making it possible to say that the respondents have an adequate set of oral health care beliefs. This study shows that the adolescents have a positive set of oral health care beliefs, which may consequently help them in attaining an optimum quality of life.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Oral health; Teeth -- Care and hygiene